Camera calibration method based on Pascal's theorem. (30th April 2019) - Wang, Xuechun; Zhao, Yue; Yang, Fengli
As one of the classical theories of projective geometry, Pascal's theorem is closely related to the conic, which is the image of a circle. A circle is the geometric element typically used as a template for camera calibration methods. In this work, we propose a calibration method based on Pascal's theorem and its inference, in which a circle is used as the calibration template. The proposed calibration method can be applied to solve the image of the circular points via the Newton iteration method. The intrinsic parameters of the camera can then be determined based on the constraints of the images of the circular points and the image of the absolute conic. The results of simulations and experiments conducted verify the validity and feasibility of the proposed calibration method.